2022
DOI: 10.1089/can.2020.0132
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Effect of Cannabidiol on Alcohol Self-Administration in Sardinian Alcohol-Preferring Rats

Abstract: Introduction: Cannabidiol (CBD) is a major cannabinoid extracted from Cannabis sativa with no abuse potential. Data from recent rodent studies suggest that amelioration of alcohol-motivated behaviors may be one of the numerous pharmacological effects of CBD. This study was designed to contribute to this research, assessing the effect of CBD on operant oral alcohol self-administration in selectively bred Sardinian alcohol-preferring (sP) rats, a validated animal model of excessive alcohol consumption. In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2022
2022
2122
2122

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 45 publications
2
6
0
Order By: Relevance
“…Differences in this aspect between these groups of animals indicate that CBD inhibited the development of tolerance to peripheral alcohol effects. This observation is in line with the results of experiments of others, clearly indicating that this compound may influence various aspects of the effects of alcohol, including the possibility of CBD-induced blockade of peripheral hypothermic EtOH activity [ 30 , 34 , 68 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Differences in this aspect between these groups of animals indicate that CBD inhibited the development of tolerance to peripheral alcohol effects. This observation is in line with the results of experiments of others, clearly indicating that this compound may influence various aspects of the effects of alcohol, including the possibility of CBD-induced blockade of peripheral hypothermic EtOH activity [ 30 , 34 , 68 ].…”
Section: Discussionsupporting
confidence: 90%
“…Studies on the interaction of CBD with alcohol have been carried out for years. Briefly, it was found that CBD administration lowered alcohol-drinking behavior in rodent models [ 34 ]. Moreover, it is postulated that its ‘anti-addictive’ action through the regulation of dopaminergic, opioidergic, serotonergic, and endocannabinoid systems, as well as observed in HIP neurogenesis, provides an interesting option for the use of this compound in the treatment of alcoholism [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“… 97 Among these is the treatment of alcohol-related problems and AUD. 98 , 99 Preclinical animal models suggest that CBD dampens preference for alcohol, alcohol seeking, 100 102 and alcohol-related functional harms, such as those to the liver and brain. 103 106 There is significantly less work examining the effects of CBD on alcohol use in humans.…”
Section: Resultsmentioning
confidence: 99%
“…These data confirm and extend previous evidence indicating the potential of CBD in attenuating discrete alcohol‐related behaviours in adult rodents (Nona et al, 2019). Indeed, CBD reduced alcohol reinforcement and consummatory behaviour in the two‐bottle choice paradigm, alcohol motivational properties and reinstatement in operant tasks, both in outbred rodents and models of genetically determined excessive alcohol drinking (Gonzalez‐Cuevas et al, 2018; Maccioni et al, 2022; Viudez‐Martínez et al, 2018). Notably, CBD administration was associated with a lower occurrence of high drinking in adolescent rats that decreased their consummatory behaviour for alcohol up to intermediate amounts (Ehinger et al, 2021), thus showing a promising effect in preventing vulnerability to excessive alcohol drinking.…”
Section: Discussionmentioning
confidence: 99%